THE PROCRASTINATION TENDENCY: A COMPARATIVE STUDY OF ACADEMIC AND NON-ACADEMIC COURSE’S LEARNERS OF AGRA CITY - Prof.Kavita Varma (International Journal of Advanced Science and Technology, 2020)
The major interest of the existing research to examine the relationship between high, average and low groups of procrastinators among learners of Academic and Non Academic courses from the colleges of Agra. The purposive random sampling used to collect data from 200 males and females from the age group of 19-28 years from different post-graduation and graduation courses of the Engineering, Management, Education and Science streams from various colleges in Agra. Procrastination scale prepared by Dr. Amit Abraham used for data collection. It is a five-point scale having total 30 statements. By using S.D., Mean, Anova and t-test the result derived which shows that significant differences are found in between Academic and Non Academic course’s learners, male and female students from the whole group (N=200). 85.5% scored Average, 10% scored high and only 4.5% scored low in procrastination trait. Out of 200 college students 171 scored average, 20 high and only 9 scored low procrastination